2011
DOI: 10.7570/kjo.2011.20.3.138
|View full text |Cite
|
Sign up to set email alerts
|

Improved Insulin Resistance, Adiponectin and Liver Enzymes without Change in Plasma Vaspin Level after 12 Weeks of Exercise Training among Obese Male Adolescents

Abstract: Background: The purpose of this study was to investigate (1) the association among anthropometric measurements, cardiopulmonary fitness, liver enzymes and inflammatory markers including vaspin levels among male adolescents, and (2) the effects of a 12 week aerobic exercise training on insulin resistance, liver enzymes and inflammatory markers including vaspin levels among obese male adolescents were also studied. Methods: We compared anthropometric and metabolic parameters between thirty obese (BMI ≧ 25) and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…283 The potential reasons for these discrepancies in these studies could be due to differences in age, BMIs and the cohorts employed. 283 Vaspin response is proposed as a compensatory mechanism to the lower insulin resistance found with obesity. 284 In support, vaspin levels correlate with fasting insulin and homeostasis model assessment of insulin resistance in individuals with obesity and also decreases with PA. 285 These data suggest that vaspin diminishes insulin resistance 285 and that PA lowers vaspin level by decreasing insulin resistance.…”
Section: Effects Of Acute and Chronic Exercise On Vaspinmentioning
confidence: 94%
See 2 more Smart Citations
“…283 The potential reasons for these discrepancies in these studies could be due to differences in age, BMIs and the cohorts employed. 283 Vaspin response is proposed as a compensatory mechanism to the lower insulin resistance found with obesity. 284 In support, vaspin levels correlate with fasting insulin and homeostasis model assessment of insulin resistance in individuals with obesity and also decreases with PA. 285 These data suggest that vaspin diminishes insulin resistance 285 and that PA lowers vaspin level by decreasing insulin resistance.…”
Section: Effects Of Acute and Chronic Exercise On Vaspinmentioning
confidence: 94%
“…277,281,282 However, a cross-sectional study found no significant differences in vaspin levels between control adolescent male subjects and individuals with obesity (BMI ≥ 25) subjected to 12 weeks of aerobic exercise. 283 However, vaspin levels were significantly associated with intima-media thickness, an early indicator of atherosclerosis. 283 The potential reasons for these discrepancies in these studies could be due to differences in age, BMIs and the cohorts employed.…”
Section: Effects Of Acute and Chronic Exercise On Vaspinmentioning
confidence: 98%
See 1 more Smart Citation
“…We initially identified 25 586 citations and, after removing duplicates, we reviewed 20 514 unique citations. Of those, 78 RCTs 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ...…”
Section: Resultsmentioning
confidence: 99%
“…Details for each individual trial are presented in eTable 3 in the Supplement . The majority of RCTs were performed in children aged 1-12 years (n = 53) 9 , 11 , 32 , 33 , 39 , 40 , 43 , 44 , 45 , 46 , 48 , 49 , 52 , 53 , 54 , 56 , 58 , 59 , 62 , 63 , 64 , 67 , 68 , 69 , 70 , 71 , 73 , 76 , 77 , 80 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 91 , 92 , 93 , 95 , 99 , 100 , 101 , 102 , 103 , 104 , 107 , 108 , 110 , 111 , 112 , 114 ; 25 were conducted in adolescents aged 13-18 years, 10 , 34 , 35 , 36 , 37 ,…”
Section: Resultsmentioning
confidence: 99%